2016
DOI: 10.1515/bjdm-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and oral health: Review of the literature

Abstract: SummaryPatients with schizophrenia, especially during period of their hospitalization, are likely to constitute a high-risk group of individuals with respect to prevalence of oral diseases. Several factors are mentioned in the manuscript that may contribute to the finding of increased prevalence of oral diseases in patients with schizophrenia. Unfortunately, some of these can be attributed to dental profession; these patients are sometimes deprived of dental service as they cannot afford the treatment due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…A recent systematic review and meta‐analysis of advanced dental disease in people with severe mental illness found that people with mental illness were 3.4 times more likely to have lost teeth than the general population and had higher rates of decayed, missing, or filled teeth . The rapidly deteriorating oral health can severely compromise patient's speech, ability to chew affecting nutrition, leads to comorbidities such as cardiovascular and respiratory diseases, and rendering the dental treatment unaffordable in later stages . Furthermore, long‐term medications in these patients may often lead to xerostomia damaging dental tissues.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review and meta‐analysis of advanced dental disease in people with severe mental illness found that people with mental illness were 3.4 times more likely to have lost teeth than the general population and had higher rates of decayed, missing, or filled teeth . The rapidly deteriorating oral health can severely compromise patient's speech, ability to chew affecting nutrition, leads to comorbidities such as cardiovascular and respiratory diseases, and rendering the dental treatment unaffordable in later stages . Furthermore, long‐term medications in these patients may often lead to xerostomia damaging dental tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, long‐term medications in these patients may often lead to xerostomia damaging dental tissues. Stigma, discrimination, limited access to treatment owing to individual and familial factors, and unwillingness of dentists to provide oral care often has catastrophic effect on oral health …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors like nature of psychiatric disorders, and oral-side effects of antipsychotic medications have been noted as contributors to poor oral health among institutionalized patients with schizophrenia [6]. In addition, unhealthy behaviors such as smoking cigarettes, alcohol consumption and drug abuse have been linked to psychiatric disorders [7]. Some studies that have been done on patients with schizophrenia focused on the assessment of dental caries and periodontal disease [8,9,10].…”
Section: Introductionmentioning
confidence: 99%